Assessing the role of primary tumour resection in patients with synchronous unresectable liver metastases from pancreatic neuroendocrine tumour of the body and tail. A propensity score survival evaluation. Issue 2 (February 2017) - Bertani, E.; Fazio, N.; Radice, D.; Zardini, C.; Spinoglio, G.; Chiappa, A.; Ribero, D.; Biffi, R.; Partelli, S.; Falconi, M.
Abstract: Background: The role of primary tumour surgery in pancreatic neuroendocrine tumours (PNETs) with unresectable liver metastases is controversial and international guidelines do not recommend surgery in such cases. Resectability of the primary tumour has never been considered in outcome comparisons between operated and non-operated patients. Methods: From two institutional prospective databases of patients affected by PNET and unresectable liver metastases, 63 patients who underwent a left-pancreatectomy at diagnosis were identified and compared with a group of 30 patients with a potentially resectable but not-resected primary tumour located in the body or tail. The endpoint was overall survival (OS). Results: The two groups significantly differed at baseline with regard to liver tumour burden Ki-67 labelling index, site of pancreas, results of the 18 FDG PET-CT and age. In the operated patients, surgical morbidity comprised 7 cases of pancreatic fistula. Postoperative mortality was nil. Median OS for patients undergoing left-pancreatectomy was 111 months vs 52 for the non operated patients (p = 0.003). At multivariate analysis after propensity score adjustment, no surgery as well as liver tumour burden>25% and higher Ki-67 index were associated with an increased risk of death during follow-up. In patients with unresectable primary tumour, OS was similar in comparison to that in the resectable but non-resected patients, and significantly worse than that in the resected patients (p = 0.032). Conclusion: In PNETs located in the body or tail and diffuse liver metastases distal pancreatectomy may be justified in selected patients. Randomized studies may be safely proposed in future on this topic.